STUDI PERENCANAAN GEOMETRIK PERKERASAN JALAN DAN PERENCANAAN ANGGARAN BIAYA PADA JALAN RAYA KALIDAWIR â€“ DESA NGUBALAN KECAMATAN KALIDAWIR - Edy Gardjito (U Karst, 2017)
So, here the author took the initiative to plane the road using flexible pavement. The hope for future, so itÂ can be use as well as possible for the local Villagers. Even There included connecting roads between several villages.The method use in this planning is a method that is often used lag other planners, namely : Book Of Directorate General of Bina marga, 1970. Regulation Of Road Geometric Planning Directorate General Of Bina Marga, 1997. Procedures for planning geometric the inter city roads, TheÂ  Center For Research and Development Jakarta, and use of others literature.The conclusion that can be get planning for this is, this way it is Â±3.200 meter with width across 7 meter. Is available is 2Â  aligment horizontal PI 1 With radisius 200 meter as big as 34Âº33,5â€™5,82â€. PI 2 radisius plan 150 meter as big as 34Âº4â€™22,29â€. With surface course pavement = 5 cm, base course = 20 cm and sub base course = 15 cm. Keyword : Road Geometric Planning, Flexible Pavement and RAB